HAMBATAN DALAM PELAKSANAAN PENDAFTARAN HAK MILIK ATAS TANAH - Udytama, I Wayan Wahyu Wira (Jurnal Yustitia, 2023)
In terms of needing land, from the legal provisions, not many people know how to obtain it andwhat is the evidence. If the land in question has the status of property rights, it will be easy to know thatthe land in question can be controlled and used indefinitely. But for someone who is going to buy land,knowledge of these things. The land mafia can be outside or inside. The type of research used is empiricallegal research. The nature of the research used is descriptive. The data collection techniques used are fieldstudy techniques and library study techniques. The data processing technique uses a qualitative descriptivetechnique. From the results of data collection and analysis, the conclusions are explained as follows:Obstacles in the implementation of registration of property rights to land at the Tabanan Regency LandOffice are caused by Government policy factors regarding tax obligations in land registration activities,Factors Lack of understanding the function and use of certificates, Assumption factors Communitiesneed expensive fees to carry out land registration, the assumption is that it takes a long time in obtainingcertificates, the assumption is that the basis for land rights owned is very strong, the publication system isnegative. Countermeasures such as: counseling/socialization on the benefits of Land Registration, carryingout the implementation of land registration with PRONA and PRODA in order to raise public awarenessand the weak economic group can obtain guarantees of legal certainty of land rights. Because it is theresponsibility of the Land Office